Examining a regulatory flexibility framework of psychological distress: Integrating distress tolerance, emotion differentiation, and emotion regulation flexibility - TNG, Germaine Yue Qi (Institutional Knowledge at Singapore Management University, 2024)
Several theoretical accounts identify emotion regulation (ER) difficulties, including poor abilities to withstand or distinguish negative emotions, as a transdiagnostic risk factor for symptoms of psychological distress. Considering this, nascent evidence hints that ER flexibility may be a mediating mechanism that explains the relationship between specific ER abilities (i.e., distress tolerance, negative emotion differentiation) and distress symptoms. Across time-lagged (Study 1) and three-wave longitudinal (Study 2) investigations of college-aged adults, a regulatory flexibility framework of distress was examined in which ER flexibility mediates the respective pathways from distress tolerance and negative emotion differentiation to psychological distress symptoms. Furthermore, we explored a reverse mediation account wherein bidirectional associations between psychological distress and ER abilities are mediated by ER flexibility (Study 2). In Study 1, self-reported, rather than task-based, ER flexibility mediated the respective pathways from distress tolerance and negative emotion differentiation to social anxiety symptoms. When ER flexibility was assessed through experience sampling in Study 2, ER flexibility (i.e., mean between-strategy variability) mediated the reversed pathway from social anxiety symptoms to negative emotion differentiation abilities. By employing a multi-method approach to assessing ER flexibility, these findings provide preliminary evidence for the proposed theoretical framework and highlight the importance of considering reciprocal associations among ER abilities, ER flexibility, and psychological distress via longitudinal designs.